A 3‐D hydrologic transport model of a water recharge system using carbamazepine and chloride as tracers. Issue 5 (22nd May 2014) - Rona, Michael; Gasser, Guy; Negev, Ido; Pankratov, Irena; Elhanany, Sara; Lev, Ovadia; Gvirtzman, Haim
Abstract Wastewater recharge facilities are often used as a final water treatment before the discharge to the sea or before water reclamation. These facilities are often located in active aquifers that supply drinking water. Thus, leakage from the water recharge facility and gradual expansion of the underground wastewater plume are of considerable health concern. Hydrological modeling of water recharge systems are widely used as operational and predictive tools. These models rely on distributed water head monitoring and at least one chemical or physical tracer to model solutes' transport. Refractory micropollutants have proven useful in qualitative identification of pollution leakages and for quantification of pollution to a specific site near water recharge facilities. However, their usefulness as tracers for hydrological modeling is still questionable. In this article, we describe a long term, 3‐D hydraulic model of a large‐scale wastewater effluents recharge system in which a combination of chloride and a refractory micropollutant, carbamazepine is used to trace the solute transport. The combination of the two tracers provides the model with the benefits of the high specificity of the carbamazepine and the extensive historic data base that is available for chloride. The model predicts westward expansion of the pollution plume, whereas a standing front is formed at the east. These trends can be confirmed by the time trace of the carbamazepine concentrations at specific locations. We show that the combination of two tracers accounts better (at least at some locations) for the evolution of the pollution plume than a model based on chloride or carbamazepine alone.